African Traditional Religion vis-à-vis the Tackle It Suffers - Nweke, Innocent Ogbonna (Journal of religion and human relations, 2021)
African Traditional Religion is the indigenous religion of the Africans. The religion that has existed before the advent of western civilization which came with secularism as an umbrella that shades Christianity, education, urbanization, colonization and so on. These features of western civilization were impressed upon African Traditional Religion. Hence, the presence of alien cultures and practices in contemporary African traditional practice, as well as the presence of elements of traditionalism in contemporary African Christian practices. This somewhat symbiosis was discussed in this paper and it was discovered that African Traditional Religion was able to jump all the hurdles of secularism, Christianity, urbanization etc and came out successfully though with bruises. The paper used socio-cultural approach in its analysis.